ANALYSIS OF EFFECT OF SUPPLY CHAIN MANAGEMENT ON FIRM PERFORMANCE OF PASSION FRUIT SYRUP - Kimberly Febrina Kodrat; Sukaria Sinulingga; Humala Napitupulu; Rika Ampuh Hadiguna (AIBPM Publisher, 2019)
Passion fruit (passifloraceae) is one of the strategic commodities because of its usefulness as raw material of passion fruit syrup as an agroindustry product that has rich nutritional value of vitamin C which is beneficial to human health. This research has five elements of supply chainnamely : farmers, suppliers, extract agroindustry, passion fruit syrup agroindustry, and retailers. The objective of this study is to analyze whether there is a significant influence between Supply Chain Management on firm performance. This type of research was a causal research. Data collection used questionnaire. From the result of multiple linear regression analysis, it showed that the variable of process integration has the biggest influence to variable of enterprise SCM performance (dependent) with coefficient value equal to (0,289), then variable of satisfaction with value (0,058), variable of trust (0,286), communication variable (0,184), dependency variable (0,021) and having the least was the variable of influence and commitment (0,080). This means that the five independent variables have a positive and significant influence on the dependent variable.